Faktor-Faktor yang Mempengaruhi Kejadian Stunting di Wilayah Kerja Puskesmas Sungai Lasi Kabupaten Solok Tahun 2024 - Ibertha Serly Novera; Lendrawati (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
Stunting or dwarfism is a chronic malnutrition problem caused by a lack of nutritional intake for a long time and is not caused by hormonal disorders or certain diseases. Data collected by SSGI West Sumatra in 2021 was recorded by the Solok District Health Service. In 2021, the working area of ​​the Sungai Lasi Community Health Center found 99 cases (13.75%) of stunting, including the highest in Solok Regency. The aim of this research is to determine the factors that influence the incidence of stunting among toddlers in the working area of ​​the Sungai Lasi Community Health Center, Solok Regency. This research design is an observational analytic with a control design. The population of this study were all toddlers in the working area of ​​the Sungai Lasi Community Health Center who were divided into two groups, namely the case group, namely toddlers who experienced stunting and the control group, namely toddlers who did not experience stunting. The sampling technique uses porpusive sampling. This research data was analyzed using SPSS. To analyze bivariate data using the chi square test and multivariate data using logistic regression. The results of this research show that parenting and sanitation patterns are related to the incidence of stunting with a p value <0.05. Birth weight, exclusive breastfeeding, immunization, history of infectious diseases and allocation of use of household funds did not have a significant relationship where the p value was >0.05.